Pengembangan Sistem Informasi Semester Antara Fakultas Ilmu Komputer Universitas Brawijaya - Winda Silviana; Denny Sagita Rusdianto; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The intermediate semester is one of the programs which has its own regulatory policies by the university, both in time determining and implementing regulation. It can be found at the Faculty of Computer Science of Brawijaya University (FILKOM UB), which is needed suitability to the prevailing business processes. There are three main processes in the intermediate semester, namely data collection, registration, and implementation. In the data collection process, there was a discrepancy between the assessor and the class that would be opened in the intermediate semester. In the registration process, there was problems with the discrepancy of interest in the course that will be taken by the participants. Based on the problems, it causes retardments in the implementation process and detrimental to stakeholder in the intermediate semester. This problems can be resolve by the web based development of intermediate semester according to procedure and user requirements using the CodeIgniter Framework with the MYSQL database, and payment gateway to make a payment transaction in realtime system. Based on requirements elicitation and analysis, the research obtained 43 functional requirements, 11 entities, and 24 data tables. The system information development resulted 100% of valid status from the whole unit testing and validation testing, and produce 100% on compatibility testing that categorized as critical issue in 11 browsers. So, the development system of intermediate semester can be run based on user requirements.